2006
DOI: 10.1080/03235400500222057
|View full text |Cite
|
Sign up to set email alerts
|

Viruses infecting field-grown tomatoes in Samsun province, Turkey

Abstract: To detect viruses infecting tomatoes and determine their incidences, surveys were conducted in 31 fields in Samsun province from May to August in 2002 and 2003. Tomato mosaic virus (ToMV), Tomato spotted wilt virus (TSWV), Potato virus X (PVX) and Cucumber mosaic virus (CMV) were detected in tomatoes after analysing 186 samples by enzyme-linked immunosorbent assay. ToMV, TSWV, PVX and CMV were detected 52.1, 12.9, 10.7 and 6.9% of the samples tested, respectively. Thirty samples (16.1%) were found to be mixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 17 publications
0
3
0
1
Order By: Relevance
“…It is important to note that the co-infection was detected in tomato and pepper areas surveyed. The mixed infection of TSWV with CMV have been reported previously (Arli-Sokmen & Sevik, 2006). The mixed infection in the host plant allows for virus interactions, resulting in genetic variation.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…It is important to note that the co-infection was detected in tomato and pepper areas surveyed. The mixed infection of TSWV with CMV have been reported previously (Arli-Sokmen & Sevik, 2006). The mixed infection in the host plant allows for virus interactions, resulting in genetic variation.…”
Section: Discussionmentioning
confidence: 83%
“…In 1998-1999, serological tests revealed that 20.2% to 7.7% of pepper samples tested were infected with CMV and 2.2% to 9.2% with TSWV in Samsun province (Arli-Sokmen et al, 2005). In 2002-2003, TSWV and CMV were detected 12.9% and 6.9% of the tested tomato crops, respectively, in the same region of Turkey (Arli-Sokmen & Sevik, 2006). CMV was detected in tomato plants in the locations of the north-west Mediterranean region of Turkey by DAS-ELISA, and the infection rate varied from 12.5% to 90.32% (Yardımcı & Eryiğit, 2006).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Bu biyotik faktörlerden bitkilerde hastalık oluşturan virüs, fungus ve bakteriler çok önemlidir. Özellikle virüslerin neden olduğu hastalıkların kimyasal mücadele ile kontrol altına alınamaması bu patojenleri daha da önemli kılmaktadır [5,6]. Domates ve biber yetiştirilen alanlarda görülen en önemli virüslerden biri domates lekeli solgunluk virüsü (TSWV)'dür.…”
unclassified